Conversion of sleeve Gastrectomy to Roux-en-Y Gastric bypass for weight loss failure - Abdul Jabbar, Mohammed Q.; Mukhtar, Ramiz S.; Abbas, Mustafa A. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Obesity is a global health issue. Laparoscopic sleeve gastrectomy has progressively become the most popular procedure among the surgical community as a definitive bariatric operation. The increasing number of surgeries performed will be likely be followed by increasing reports of patients experiencing weight loss failure.Objectives: To determine the effectiveness of conversion from laparoscopic sleeve gastrectomy to Roux-en-Y gastric bypass in cases with weight loss failure.Patient &methods: The retrospective review of patients who had operated with laparoscopic sleeve gastrectomy from October 2009 to January 2016 at Saint Raphael hospital, 21 patients included in this study had insufficient weight loss after Sleeve Gastrectomy and converted to Roux-en-Y gastric bypass.Results: Fifteen patients (71.4%) had LSG as their single bariatric operation before conversion to roux en Y gastric bypass, 2 patients (9.5%) had Intragastric balloon and 4 (19.1%) patients had the laparoscopic adjustable gastric band before to their sleeve gastrectomy. Fourteen patients (66.6%) were female and 7 (33.4%) were males, At 6, 12, 18 months after bypass ,mean BMI was 37.2 (32.7-44.3),32.5(28.7-39.1) and 30.2 kg/m2 (24.3-37.9 kg/m2) respectively , reflecting a %EWL (percentage weight loss) at 18 month of 61.7%.Conclusion: insufficient weight loss after Sleeve Gastrectomy can be safely and effectively treated by conversion to Roux-en-Y gastric bypass to control weight loss failure or weight regain.Keywords: weight loss failure, weight regain, failed Sleeve Gastrectomy.